Analisis Strategi Non-Performing Financing (Studi kasus pada BMT Nagari Lasi Kecamatan Candung Kabupaten Agam) - Syaleh, Hariman (Jurusan PIPS FKIP UMMY Solok, 2018)
This study aims to analyze Non-Performing Financing Strategies Case Studies In BMT Nagari Lasi Candung District Agam regency, from the results of research that the authors find in the field by using the population in this study all customers financing BMT Nagari Lasi, 105 people. From the results of data obtained from respondents processed by using SPSS program with stages through the test research instrument is the validity test , reliability, descriptive respondents, classical assumption test, to multiple linear regression analysis. From the results of multiple linear regression analysis the authors found that of the three independent variables that the author carefully that the interest rate loan margin has a positive and significant influence on the principle of financing. Then the second variable of the loan term has a positive and significant influence on the principle of financing. The variable of customer sales stability has a positive and significant influence on the financing principle. Then seen from the results of the test f showed that the variable interest rate margin loan, loan term and stability of customer sales simultaneously have a positive and significant impact on the principle of financing. The result of determinant coefficient test shows that there are many other variables that influence the financing principle in BMT Nagari Lasi Candung Subdistrict of Agam Regency so it is expected for the next researcher to add another variable from the author's precise variable for the perfection of research in the field of financing principle.